Manajemen Pembelajaran Aqidah Akhlak di Madrasah Ibtidayah Negeri 9 Aceh Timur - Marlinda Marlinda; Nurhayati Nurhayati; Zurriyati Zurriyati (Journal of Islamic Education Leadership, 2023)
Management of Aqidah Akhlak Learning in Madrasah Ibtidayah Negeri 9 East Aceh. This research is entitled "Management of Aqidah Akhlak Learning in Madrasah Ibtidayah Negeri 9 East Aceh". The formulation of the problem is: How to plan, implement and evaluate the learning of aqidah morality in MIN 9 East Aceh. This study aims to explain the planning, implementation and evaluation of moral aqidah learning in MIN 9 East Aceh. This research is a field research with a qualitative approach using descriptive methods, to make a systematic, factual and actual description of the facts, nature and relationships between existing phenomena. Data collection techniques by means of in-depth interviews and text analysis. Based on the implementation of the learning implementation plan (RPP) and the Aqidah Akhlak Learning Syllabus at MIN 9 East Aceh, it has also gone well. In this implementation, using learning media that are relevant to learning aqidah morals at MIN 9 East Aceh has been carried out well. Analyzing the Curriculum, Semester Program and Annual Program, it was found that the evaluation conducted by MIN 9 Aceh Timur in learning the students' moral aqidah was good. Because the achievement of the learning success of students' moral aqidah has been measured well. In analyzing the learning implementation plan (RPP) and Aqidah Akhlak learning syllabus at MIN 9 East Aceh, the assessment was carried out through several aspects, namely Class-Based assessment paying attention to three domains, namely knowledge (cognitive), attitude (affective), and skills (psychomotor). Analyzing the relevant learning media used by Aqidah Akhlak teachers at MIN 9 East Aceh are student attendance, giving questions in the form of multiple choice, essays, and portfolios, as well as assessments of students' thinking skills. Based on this, analyzing the relevant learning media in learning aqidah morals at MIN 9 East Aceh has been evaluated properly